Copolymers of methyl methacrylate and a palm oil-based macromer as dental materials / Nurshafiza Shahabudin - Nurshafiza, Shahabudin (2011)
This dissertation describes the study using a specific palm kernel oil macromer, namely FA35 to modify the poly(methylmethacrylate) (PMMA) in attempt to enhance its properties of as a denture base polymer. This study is divided into two sections: (I) Characterization and copolymerization of FA35 macromer and methyl methacrylate (MMA), and (II) Evaluation of the copolymers as a denture base material. Copolymerization of macromer and MMA was carried out by solution and bulk processes. Both methods used benzoyl peroxide as initiator. This macromer-MMA copolymerization process was stable at 80°C for solution technique. Lower temperature was sufficient for bulk method which was from 60-70°C during the process of producing the pre-polymer syrup and 60°C for overnight curing. At the end of the reaction, the mixture was heated to 100°C for one hour to evaporate off residual monomer. Fourier Transform Infra Red (FTIR) analysis and thermal characterization of the copolymers confirmed that they contained repeating units from both macromer and MMA. Addition of cross-linking agent, ethylene(glycoldimethacrylate) or EGDMA did not significantly affect the Tg of the copolymers. Differential Scanning Calorimetry (DSC) analysis showed single value of Tg was obtained for each copolymer. Copolymers containing up to 20% w/w of macromer unit showed significantly lower water sorption. In addition, solubility of crosslinked copolymer (Group B) was relatively low and comparable with the solubility of the commercial resin. Mechanical test revealed that incorporation 5-10% w/w of macromer has significantly improved the impact and flexural strength of the PMMA, but further increase of macromer beyond 15% w/w progressively lowered the mechanical strength of copolymers. Visual inspection was performed to iv determine type of fracture in the copolymers, from the two fragments resulting from the flexural test. Both broken fragments could be repositioned at the fractured line, presenting a smooth surface; hence the fractures were classified as brittle. Overall, the experimental copolymers which contained a noteworthy amount of non-petroleum based materials derived from palm oil increased the mechanical strength of acrylic resin.